Evolution of Relaxor Behavior in Multiferroic Pb(Fe2/3W1/3)O3-BiFeO3 Solid Solution of Complex Perovskite Structure. Issue 1 (January 2021) - Li, Haijuan; Zhuang, Jian; Bokov, Alexei A.; Zhang, Nan; Zhang, Jie; Zhao, Jinyan; Ren, Wei; Ye, Zuo-Guang
Abstract: Mutiferroic materials like bismuth ferrite BiFeO3 have attracted much interest in the last decade due to their promising potential for such applications as spintronics and magnetoelectric data storage devices. On the other hand, relaxor ferroelectrics have been intensively studied for their complex structures with quenched disorder and polar nanoregions which play an important role in their outstanding piezoelectric performance. Much less studied are the single-phase multiferroics that exhibit ferroelectric and/or magnetic relaxor behavior and the correlation between their structure and intricate magneto-electric interactions. In this work, we investigate the evolution of the structure and relaxor behavior in the solid solution between the complex perovskite multirelaxor Pb(Fe2/3 W1/3 )O3 [PFW] and canonical multiferroic BiFeO3 [BFO], (1- x )PFW- x BFO (with a solubility limit of x = 0.30). The temperature dependences of the dielectric permittivity and loss tangent measured in the frequency range from 100 Hz to 1 MHz indicate characteristic relaxor ferroelectric properties for compositions of x ≤ 0.15, with a frequency-dependent dielectric permittivity peak and its temperature, Tm, satisfying the Vogel-Fulcher law. Detailed studies of the evolution of the relaxor behavior with composition reveal that Tm decreases firstly with a small amount ( x = 0.05) of BFO substitution and then increases with further increase of BFO concentration. The degree of relaxor character, as defined by Δ Tm [ Tm (1 MHz) - Tm (100 Hz)], increases monotonously with increasing BFO content, signifying an enhancement of relaxor behavior with BFO substitution, which is confirmed by the Lorenz-type quadratic variation of the static permittivity. A temperature - composition phase diagram is constructed in terms of the characteristic Burns temperature ( TB ) and freezing temperature ( Tf ), which delimits a paraelectric state (PE) above TB, a non-ergotic relaxor state (NR) below Tf, and an ergotic relaxor state (ER) in between. The observed enhancement of relaxor behavior is explained by an increase in the number and size distribution of polar nanoregions in the ER phase, resulting from increased compositional and charge disorders as a result of BFO substitution. The evolution of relaxor behavior and its microscopic mechanisms studied in this work are insightful for a better understanding the multirelaxor properties in multiferroics. Moreover, further substitution of BFO ( x ≥ 0.2) flattens the permittivity curves and leads to a temperature-stable variation of high dielectric constant (≈ 10 3 ) in a wide temperature range, making the PFW-BFO solid solution attractive for such applications as high energy density capacitors.